(untitled) (Educational Knowledge, 2020)
The purpose of this study is to identify the main factors considered by students from the 2019 cohort (all first-year students) at the Chiloé campus of the University of Los Lagos, located in Castro-Ancud, when choosing a higher education institution. It also aims to determine which factors influenced their choice of major: social, academic, economic, and interpersonal. An explanatory, non-experimental, and quantitative paradigm was used to obtain the most objective data possible. A survey was used to collect and subsequently analyze the quantitative data. The results indicate that the most important factor for students is access to scholarships and benefits offered by higher education institutions. Finally, several actions are proposed, the main one being the strengthening of ties with the Educational Establishments of the Province, in order to carry out activities to help students graduating from their classrooms, such as assisting in obtaining scholarships or preparing for the general admission tests of Chilean universities.